Exploring the association between healthy lifestyle score and atherogenic indices in a general population of Iranian adults - Reza Amani-Beni; Bahar Darouei; Noushin Mohammadifard; Awat Feizi; Motahare Bateni; Fahimeh Haghighatdoost; Maryam Boshtam; Narges Grau; Nizal Sarrafzadegan (Lipids in Health and Disease)
Abstract Background Atherogenic indices outperform traditional lipid markers; however, the combined association of lifestyle habits with these indices remains unclear. This study, which is based on population data, explored the link between the Healthy Lifestyle Score (HLS) and various atherogenic indices. Methods In this cross-sectional analysis of the 2013 Isfahan Cohort Study 2 (participants aged ≥ 35 years), HLS was derived from four factors: smoking status, body mass index (18.5–24.9 kg/m²), physical activity (≥ 1350 MET minutes/week), and diet quality (top two quintiles of the Alternate Healthy Eating Index-2010). Each factor was scored as 1 for adherence and zero otherwise, yielding a score of 0–4. The atherogenic indices included the Atherogenic Coefficient (AC), Atherogenic Index of Plasma (AIP), Atherogenic Combined Index (ACI), Castelli Risk Indices I and II (CRI-I/II), non-high-density Lipoprotein Cholesterol (NHC), Lipoprotein Combined Index (LCI), Remnant Lipoprotein Cholesterol (RLPC), and triglyceride/high-density lipoprotein cholesterol (TG/HDL-C) ratio. Logistic and linear regression analyses were conducted to examine these associations after adjusting for confounders. Results Among 2,256 participants (49.7% men), the overall mean age was 58.15 ± 9.89 years. Across the population, a higher HLS was strongly linked to a decreased likelihood of elevated levels of individual atherogenic indices. Compared to individuals with HLS 0–1, those with HLS 3–4 had notably reduced odds of high AIP (odds ratio (OR): 0.42; 95% CI: 0.30–0.59), ACI (OR: 0.60; 95% CI: 0.47–0.77), and other indices (all P for trend < 0.05). Sex-stratified analyses revealed distinct patterns: in men, HLS was strongly associated with lower TG/HDL-C, AIP, and ACI, whereas in women, stronger associations were observed with cholesterol-driven markers (AC, NHC, RLPC, CRI-I, and CRI-II). Linear regression analysis confirmed that each unit increase in HLS corresponded to lower continuous values of these indices in the total population. AIP emerged as the most sensitive marker in both sexes. Conclusions Adherence to a healthier lifestyle, as measured by the HLS, was significantly associated with lower atherogenic indices, highlighting its role in reducing cardiovascular risk. These results support integrating lifestyle interventions with cardiovascular prevention. Future studies should assess the causal impact of lifestyle modifications on atherogenic profiles.